The Palace Settlement in the Kazan Region in the XVI-XVII Centuries - Marina Maratovna Imasheva, Dina Abdulbarovna Mustafina, Marat Salavatovich Gatin,; Dzhabbarovna Novikova, Irma (Opción, 2019)
The aim of the article is to determine the spatial organization of Palace settlements in the Kazan region in the XVI-XVII centuries. The methods of investigation are system approach and system analysis. In result, in the second half of the XVI century, the vicinity of fortified settlements became the place of compact residence of palace peasants in the Middle Volga region; and secondly – coastal lands of Kama river basin’s rivers. In conclusion, the localization and tracing of palace settlements serve as a marker that denotes the main direction of the colonization process which coincided with the vector of domestic policy